Natural polysaccharide-based aerogels and their applications in oil–water separations: a review. Issue 15 (30th March 2022) - Fu, Ye; Guo, Zhiguang
Abstract : This paper reviews the polysaccharide-based aerogels reported in recent years for oil–water separation, compares their efficiency in the oil–water separation process, and provides ideas for the preparation of green oil–water separation materials. Abstract : With the development of the economy and the progress of industrialization, the problem of water pollution has become very serious. Crude oil leakage at sea, petroleum industry wastewater, and domestic grease wastewater have all caused serious oily wastewater, which has seriously affected the ecological environment and caused huge economic losses. The development of materials for the effective treatment of oily wastewater is a significant means to handle this problem. In recent years, various types of aerogels have been prepared and used in the field of oil–water separation. Natural polysaccharide-based composite aerogels have attracted widespread attention due to its wide range of raw materials, low cost, environmental protection, and microbial degradation. Its excellent performance also provides new ideas and directions for the manufacture of efficient, green, and cheap oil–water separation materials. In this article, polysaccharide-based composite aerogels and their applications in the field of oil–water separation in recent years are reviewed. The article mainly includes the summary of aerogels, preparation of polysaccharide-based aerogel materials and technology, performance evaluation, and application in the field of oil–water separation. Finally, the challenges faced by polysaccharide-based aerogels in practical applications are briefly discussed and the future development direction of aerogels has been presented.